Marketing in the anthropocene: A future agenda for research and practice - Nancy M. P. Bocken; Laura Niessen; Maike Gossen; Ankita Das; Maria Zielińska (AMS Review, 2025)
Marketing is an important function and practice in everyday business. It involves getting potential customers interested in a product or service through value-oriented arguments. In this way, marketing plays a pivotal role in driving the consumption of goods and services. Given the increasing consumption of goods and services, decreasing product lifetimes, and increasing levels of waste in all product categories, it is evident that the practice and theory of marketing needs a radical rethink in light of pressing resource and climate issues. The impact of unsustainable production and consumption patterns has led to this era being referred to as the Anthropocene, in which humans have become the dominant influence on the climate and the natural environment. There is an urgent need to take a new direction to adapt marketing theory and practice to these pressing global needs. In this study, we investigate the following questions: What role should marketing play in the era of the Anthropocene? What concepts, outcomes, tools and theories does marketing offer to support a transition towards Marketing in the Anthropocene? We conduct a scoping literature review based on different research directions and propose a conceptualization for "Marketing in the Anthropocene" as an inspirational, forward-looking concept, tool and practice for marketers and marketing researchers. We highlight relevant marketing tools and theories and provide guiding questions for future research and practice.
Keywords: 330; Marketing; Strong sustainability; Sufficiency; Climate change; Regeneration; Anthropocene; Research agenda